Dementia in Parkinson's Disease Everything you Need to Know - Zhang, Lin; Olichney, John M. (IntechOpen, 2022)
An estimated 50% to 80% of individuals with Parkinson's disease experience Parkinson's disease dementia (PDD). Based on the prevalence and clinical complexity of PDD, this book provides an in-depth update on topics including epidemiology, diagnosis, and treatment. Chapters discuss non-medical therapies and examine views on end-of-life issues as well. This book is a must-read for anyone interested in PDD whether they are a patient, caregiver, or doctor.